EPR-spectroscopy of the fast proton exchange reactions in solutions - Masalimov, A.S.; Kurmanova, A.F.; Nikolskiy, S.N.; Ospanov, A.U.; Tur, A.A. (KSU Publ., 2014)
Kinetic parameters of the fast intermolecular proton exchange reactions between radical 3,6-di-tert.butyl-2- oxyphenoxyl and different H-acids in toluene solutions obtained by ESR spectroscopy method are presented. NH-acids have more protolytic reactivity than carboxylic acids. Values of various physico-chemical properties for some H-acids, such as ionization potential, electron affinity, proton affinity and energy of deprotonation were obtained by quantum chemical calculations in the program «Gaussian-2009».
Ерітінділердегі жылдам протон алмасу реакцияларының ЭПР-спектроскопиясы
ЭПР-спектроскопия быстрых реакций протонного обмена в растворах
Keywords: EPR-spectroscopy; semiquinone radicals; H-acids; proton exchange reactions; quantum-chemical investigations